Persian cats under first opinion veterinary care in the UK: demography, mortality and disorders - O'Neill, Dan G; Romans, Charlotte; Brodbelt, Dave C; Church, David B; Černá, Petra; Gunn-Moore, Danièlle A (Scientific reports, 2019)
Persian cats are a popular cat breed worldwide, and especially in the US, Europe and Asia. This study aimed to describe the demography, common disorders and mortality in Persians under general practice veterinary care in 2013 in the UK. The study population of 285,547 cats overall included 3235 (1.1%) Persians. Mean adult Persian bodyweight was 3.9 kg (SD 0.9) and median age was 7.0 years (IQR 3.3-11.6). At least one disorder was recorded in 2099 (64.9%) Persians. The most common specific disorders were haircoat disorders (411, 12.7%), periodontal disease (365, 11.3%), overgrown nails (234, 7.2%), and ocular discharge (188, 5.8%). The most common disorder groups were dermatological (578, 17.9%), ophthalmological (496, 15.3%) and dental (397, 12.3%). Median longevity was 13.5 years (IQR 9.9-16.0). The most common grouped causes of death were renal disease (102, 23.4%), neoplasia (37, 8.5%) and mass-associated disorder (35, 8.0%). This is the first study to use general practice data to examine the overall health of Persian cats. With haircoat, ocular and dental disorders being the predominant disorders identified, this study highlights the need for increased owner awareness to manage and prevent the typical health problems associated with this breed's phenotype.
Keywords: Demography; Sex Factors; kočky; druhová specificita; prevalence; Female; Longevity; věkové faktory; Spojené království; zvířata; Cat Diseases; nemoci koček; United Kingdom; sexuální faktory; ženské pohlaví; Male; Veterinary Medicine; dlouhověkost; Species Specificity; demografie; Prevalence; Cats; Age Factors; Animals; mužské pohlaví; veterinární lékařství